14-3-3 promotes sarcolemmal expression of cardiac Ca V 1.2 and nucleates isoproterenol-triggered channel superclustering - Heather C. Spooner; Alexandre D. Costa; Maartje Westhoff; Adriana Hernández-González; Husna Ibrahimkhail; Vladimir Yarov-Yarovoy; Mary C. Horne; Eamonn J. Dickson; Rose E. Dixon (Proceedings of the National Academy of Sciences, 2025)
The L-type Ca 2+ channel (Ca V 1.2) is essential for cardiac excitation–contraction coupling. To contribute to the inward Ca 2+ flux that drives Ca 2+ -induced-Ca 2+ -release, Ca V 1.2 channels must be expressed on the sarcolemma; thus the regulatory mechanisms that tune Ca V 1.2 expression to meet contractile demand are an emerging area of research. A ubiquitously expressed protein called 14-3-3 has been proposed to affect Ca 2+ channel trafficking in nonmyocytes; however, whether 14-3-3 has similar effects on Ca V 1.2 in cardiomyocytes is unknown. 14-3-3 preferentially binds phospho-serine/threonine residues to affect many cellular processes and is known to regulate cardiac ion channels including Na V 1.5 and the human ether-à-go-go–related gene (hERG) potassium channel. Altered 14-3-3 expression and function have been implicated in cardiac pathologies including hypertrophy. Accordingly, we tested the hypothesis that 14-3-3 interacts with Ca V 1.2 in a phosphorylation-dependent manner and regulates cardiac Ca V 1.2 trafficking and recycling. Confocal imaging, proximity ligation assays, superresolution imaging, and coimmunoprecipitation revealed a population of 14-3-3 colocalized and closely associated with Ca V 1.2. The degree of 14-3-3/Ca V 1.2 colocalization increased upon stimulation of β -adrenergic receptors with isoproterenol. Notably, only the 14-3-3-associated Ca V 1.2 population displayed increased cluster size with isoproterenol, revealing a role for 14-3-3 as a nucleation factor that directs Ca V 1.2 superclustering. Isoproterenol-stimulated augmentation of sarcolemmal Ca V 1.2 expression, Ca 2+ currents, and Ca 2+ transients in ventricular myocytes were strengthened by 14-3-3 overexpression and attenuated by 14-3-3 inhibition. These data support a model where 14-3-3 interacts with Ca V 1.2 in a phosphorylation-dependent manner to promote enhanced trafficking/recycling, clustering, and activity during β -adrenergic stimulation.